Procesos y experiencias en las prácticas de terapia ocupacional en comunidad en Argentina - Vinzón, Valentina (Universidade Federal de São Carlos, 2018)
The recent history of the Occupational Therapy (OT) in Latin America shows great concern for socio-community issues that affect occupations and the daily life of individuals and communities. The occupational therapist, acting in society with the demands that it imposes, must promote possibilities of inclusion, emancipation and participation in people’s social life. Thus, the community as a context of participation to achieve a collectively-built state of well-being, and as a fundamental space of practice and visibility of the OT, requires further studies on this discipline. To be able to make a critical contribution to this area, it is fundamental to analyze, from the perspective of the service users and the occupational therapists of community settings, the effects generated by the interventions as perpetuators or transformative elements of the social realities of people and their communities. The present study, qualitative, is positioned in the socio-critical perspective to describe and analyze the processes and experiences of people who participate in OT programs at the community level, in relations to the changes they generate in their daily lives and life projects, and to know how occupational therapists co-produce these practices. To achieve this objectives, we start with a scoping review of the relevant literature to understand from what foundations and methodologies occupational therapists have been developing their practices in community in the last years (2006-2016). In a second stage, and because it is a collaborative research, we worked from three different occupational therapy programs in community settings of the city of Santa Fe and surroundings, in Argentina. Participant observations, interviews with service users and occupational therapists were carried out, as well as an adaptation of the Photovoice methodology. The results show that the OT community practices studied -linked to social and solidarity economy-, constitute a fundamental space of participation for the users, in the construction of conditions for socio-economic autonomy, the creation of links of support, and the projection of a future of possibilities. Also, from the perspective of the occupational therapists, the co-construction processes of these practices and their actual conditions are described.

La historia reciente de la Terapia Ocupacional (TO) en Latinoamérica muestra una preocupación creciente por las problemáticas socio-comunitarias que afectan las ocupaciones y el cotidiano de las personas. El terapeuta ocupacional actuando en la sociedad con las demandas que ésta impone, debe promover posibilidades de inclusión, emancipación y participación en la vida social de las personas. Así, la comunidad como contexto de participación para lograr un bienestar construido conjuntamente y como espacio fundamental de práctica y visibilización de la TO, requiere más estudios y profundizaciones en la disciplina. Para continuar contribuyendo a esta área de una manera crítica, sostenemos que es fundamental analizar, desde la óptica de usuarias y usuarios, así como de terapeutas ocupacionales de los servicios comunitarios, los efectos que generan las intervenciones, como perpetuadoras o transformadoras de las realidades de las personas y sus comunidades. Este estudio, cualitativo, se posiciona en la perspectiva socio-crítica para describir y analizar los procesos y las experiencias de quienes participan en propuestas de TO a nivel comunitario, en relación con los cambios que éstas generan en su cotidiano y proyectos de vida, y también, conocer cómo las/os terapeutas ocupacionales co-construyen dichas prácticas. Para alcanzar estos objetivos se partió de una revisión panorámica de literatura, para conocer desde qué fundamentos y metodologías las terapeutas ocupacionales vienen desarrollando las prácticas en comunidad en los últimos años (2006-2016). En una segunda etapa, se realizó una investigación colaborativa estudiando tres propuestas de TO en ámbitos comunitarios de la ciudad de Santa Fe y alrededores (Argentina). Se realizaron observaciones participantes, entrevistas a usuarias/os y terapeutas ocupacionales y se implementó una adaptación de la metodología Photovoice. Los resultados muestran que estas prácticas comunitarias de TO -vinculadas con la economía social y solidaria-, constituyen un espacio de participación fundamental para las/os usuarias/os, en la construcción de condiciones para la autonomía socio-económica, la formación de vínculos de soporte, la proyección de un porvenir de posibilidades. Asimismo, desde la perspectiva de las terapeutas ocupacionales, se describen los procesos de co-construcción de dichas prácticas y sus condiciones actuales.
Processes and experiences in the community practices of occupational therapy, in Argentina
Processos e experiências nas práticas comunitárias da terapia ocupacional, na Argentina
Keywords: Práticas de Terapia Ocupacional; Comunidade; Usuários e usuárias; Terapeutas ocupacionais; Processos e experiências; Prácticas de Terapia Ocupacional; Comunidad; Usuarios y usuarias; Terapeutas ocupacionales; Procesos y experiencias; Occupational Therapy Practices; Community; Service users; Occupational therapists; Processes and experiences; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL